Legal Confıscatıon as a Property Rıght Issue in Turkey - Guloglu, Yavuz (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
Zoning plans are drawn and written texts prepared as a result of planning activities according to the characteristics of the region in order to meet the social, cultural, human and economic needs of a settlement and to show a safer and more regular development of the place. The property rights of individuals can be restricted by means of the plans prepared by the administration to create livable, orderly and modern living spaces. While the zoning plans are being prepared, the immovables allocated for public services should first be selected from public lands and if these immovables are not sufficient for the places to be allocated to the public service areas, the immovables subject to private property should be allocated to the public service and these areas should be expropriated by the administrations to be allocated on their behalf. The Zoning Law No. 3194 in Turkey is the basic regulation of the zoning law. In the Zoning Law, there is a regulation that the parcels allocated to public services in the zoning plans will be expropriated within five years. However, if the expropriation of the immovables is not completed within the time specified in the legal regulation, the owner who is deprived of his right to dispose of the immovable, is unfairly burdened with a heavy burden. The concept of